Mediating role of relationship quality between customer experience, perceived value, and sustainable intention in the online transportation industry - Gilang Pratama Hafidz; Even Hendrian (Journal of Enterprise and Development (JED), 2023)
Purpose — This study aims to investigate the direct and indirect relationship among customer experience, perceived value, and relationship quality on sustainable intention within the online transportation industry.Method — Data were collected from 310 respondents, aged 17 years old and over, who had used its services at least twice in the past month and are domiciled in Jabodetabek. The data were analyzed using PLS-SEM.Result — The results of this research showed that perceived value has a positive effect on relationship quality. Customer experience positively affects perceived value, and customer experience also positively affects sustainable intention. Additionally, perceived value has a positive influence on sustainable intention, but customer experience does not affect relationship quality. Similarly, relationship quality has no effect on sustainable intention. Furthermore, relationship quality has not been proven to mediate either the relationship between perceived value and sustainable intention or the relationship between customer experience and sustainable intention.Contribution — The academic contribution of this study lies in its emphasis on a specific and novel research focus. Unlike previous studies that have taken a broad approach to investigating social media commerce, this research introduces a distinctive perspective by narrowing its scope exclusively to the online transportation application.